Entrepreneurship Socialization as a Strategy to Empower Housewives and Strengthen Family Economic Independence in Tarowang Village, Jeneponto - Muhammad Ichwan Musa; Uhud Darmawan Natsir; Abd Muis; Wiwin Riski Windarsari; Andi Ariyani Hardianti (Yayasan Literasi Sains Indonesia, 2025)
This community engagement activity was conducted in Tarowang Village, Jeneponto Regency, to strengthen the economic independence of housewives through entrepreneurship socialization. The background of this program stems from the limited income opportunities for women in rural areas, where most households depend on traditional agriculture. The main objectives were to enhance the entrepreneurial knowledge and skills of housewives, reduce gender-based economic disparities, and promote the establishment of sustainable micro-enterprises. The methods applied included entrepreneurship socialization, interactive workshops, mentoring sessions, and practical training on business planning, production, marketing, and financial management. The activity involved 35 housewives as participants, of whom 90% reported a significant increase in entrepreneurial knowledge, and 70% showed improved confidence in managing small businesses. After the training, 12 participants successfully initiated home-based enterprises, such as snack production, traditional crafts, and herbal beverage processing, contributing to an average increase of 25% in household income. The results indicate that entrepreneurship socialization effectively enhances women’s participation in local economic activities and fosters a culture of self-reliance. The program’s impact extends beyond economic gains, as it builds social networks, improves decision-making roles for women, and encourages long-term community resilience. Overall, this activity contributes meaningfully to community empowerment by promoting inclusive and sustainable entrepreneurship as a driver of rural economic development.